Paradigma Hukum Dalam Perspektif Taqi Al-Din Al-Subki - Taufik Setyaudin (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2023)
The elements contained in a paradigm become a mode of thought, mode of inquiry, and mode of knowing. Through this paradigm, it will be seen how the conception and systematic thinking of scientists when looking at an object or a certain framework in understanding something. In the paradigm of Islamic law, there are broad and permissive legal principles and provisions, leaving room for human existence related to social and historical developments.Al-Subki was a Qadi, appointed by the Mamluk sultan, subject to a condition (whether express or implied) that necessitated restrictions on the Shafi'i school of thought. In addition, al-Subki is a mujtahid fi al-mazhab, that is, someone who is able to build a paradigm of rational law based on the elements of ikhtilaf in a school